2022
DOI: 10.1111/bjd.21679
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with Staphylococcus aureus in healthcare workers: consequences of hand eczema

Abstract: Conflicts of interest: S.G.K. is an advisory board member/consultant for AbbVie, Celldex Therapeutics, Galderma, Incyte, Pfizer, Regeneron Pharmaceuticals and Kiniksa Pharmaceuticals, and has served as an investigator for Galderma, Kiniksa Pharmaceuticals, Pfizer Inc. and Sanofi; the other authors declare they have no conflicts of interest.Data availability: further information regarding the data and its purchase are available through the Healthcare Cost and Utilization Project (Agency for Healthcare Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…HE may facilitate the transmission of pathogens from HCWs to patients and thus hospital‐acquired infections. A recent study found that 10% of HCWs with HE were colonized with Staphylococcus aureus compared to 1% of HCWs without HE 7 and previously, it was shown that colonization with methicillin‐resistant Staphylococcus aureus is not uncommon in HCWs with HE 8 …”
Section: Introductionmentioning
confidence: 92%
“…HE may facilitate the transmission of pathogens from HCWs to patients and thus hospital‐acquired infections. A recent study found that 10% of HCWs with HE were colonized with Staphylococcus aureus compared to 1% of HCWs without HE 7 and previously, it was shown that colonization with methicillin‐resistant Staphylococcus aureus is not uncommon in HCWs with HE 8 …”
Section: Introductionmentioning
confidence: 92%